The Use of Mobile Applications to Support Indigenous Youth Wellbeing in Canada - Noronha, Noella; Smith, Savanah J.; Martin Hill, Dawn; Davis Hill, Lori; Smith, Sara; General, Amy; McQueen, Cynthia; Looking Horse, Makaśa; Drossos, Alexander; Lokker, Cynthia; Bilodeau, Nicole M.; Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2021)
In Canada, Indigenous youth have remained resilient despite being confronted with a wide range of structural and systemic risks, such as long-lasting boil water advisories, over-representation in the child welfare system, and injustices related to land treaties. As people of the land, all disruptions to ecological health are a disruption to personal and community holistic health. Land-based activities and cultural continuity strengthen pathways of perseverance for Indigenous youth (Toombs et al., 2016). For youth, cultural self-expression and personal agency are enhanced with digital platforms, which are well-suited to Indigenous people’s strengths in art, music, and oral forms of passing on knowledge. The field of mental health has turned to e-supports such as mobile applications (apps) that can provide easy-to-access intervention, when needed. To date, resilience interventions have received comparatively less attention than the study of resilience factors and processes. It is timely to review the extant literature on mental health apps with Indigenous youth as, currently, Indigenous apps are in early research stages. Critically reviewing work to date, it is argued that an inclusive and expansive concept of resilience, coherent with Indigenous holistic health views, is well-positioned as a foundation for collaborative resilience app development. To date, few mental health apps have been researched with Indigenous youth, and fewer have been co-constructed with Indigenous youth and their community members. The current literature points to feasibility in terms of readiness or potential usage, and functionality for promoting an integrated cultural and holistic health lens. As this effort may be specific to a particular Indigenous nation’s values, stories, and practices, we highlight the Haudenosaunee conceptual wellness model as one example to guide Indigenous and non-Indigenous science integration, with a current project underway with the JoyPopTM mHealth app for promoting positive mental health and resilience.